Efeito dos sistemas de produção orgânico e convencional na qualidade nutricional de alface dos grupos lisa, crespa e americana - Souza, André Luiz Gomes de (2012)
The nutritional quality of vegetables is related to the management practices adopted in production systems. According to theory Trofobiose conventional production systems may affect the development of plants providing higher levels of free amino acids and soluble sugars making vegetables more vulnerable to attack by pests and disease manifestations by facilitating the availability of nutrients. The objective of this study was to evaluate the effects of production systems on conventional and organic compound levels of primary and secondary metabolism of lettuce groups Lisa Crespa and Americana. Groups of lettuce produced in organic and conventional farms were collected in the wild region of Sergipe in two production cycles. For each production system and cycle were collected 10 heads of lettuce Lisa Crespa and Americana. The data were analyzed levels of chlorophyll, carotenoids, total phenols, total organic acids, ascorbic acid, protein, nitrate, ash, fiber and soluble solids, determining the activity of polyphenol oxidase and phenylalanine ammonia-lyase. The analyzes were performed with five repetitions of each system and the production cycle. It was found in all groups lettuce than the conventional system can reduce the levels of bioactive compounds, and antioxidants, to the time which can provide increased levels of soluble solids. Lettuce American group showed the greatest effects related to production systems having a more severe nutritional quality and thus can be regarded as less suitable conventional production systems compromise by providing a greater degree of vitamins and provitamins. The organic production system contributed to the nutritional potential of lettuce groups Lisa, and American Crespa favoring the levels of bioactive compounds and antioxidants compared to those grown in conventional production system.